Development of Interactive Learning Media Using Heyzine Flipbook on Indonesian Language Learning in Elementary School - Robiatul Munajah; Meilani Anggraini (AL-ISHLAH: Jurnal Pendidikan, 2025)
The development of interactive learning media plays a crucial role in enhancing students' learning experiences. This study investigates the development, feasibility, and effectiveness of Heyzine Flipbook as an interactive learning medium in Indonesian language learning for elementary school students, particularly in improving early reading skills. A Research and Development (RD) approach was used, following the Borg Gall model, implementing 7 out of 10 stages. The study involved 21 first-grade students from SDN Cipinang Besar Selatan 20 Pagi. The Heyzine Flipbook, an open-access platform for converting PDFs into interactive digital books with multimedia components (audio, video, and web links), was utilized. The feasibility of the Heyzine Flipbook was validated by experts, with scores of 82.86% from media experts, 95.24% from material experts, and 95% from language experts, indicating high feasibility. The effectiveness was assessed through pre-test and post-test scores. The average pre-test score was 78.33, which increased to 89.33 in the post-test, demonstrating a significant improvement in early reading skills. The results indicate that Heyzine Flipbook is an effective interactive learning medium for elementary students, enhancing engagement and comprehension in Indonesian language learning. The study confirms that Heyzine Flipbook is a feasible and effective tool for improving early reading skills in elementary schools. Further research is recommended to explore its application in other subjects and grade levels.